Utilization of Furniture Waste Into Handicrafts that Produce Selling Value in Beratwetan Village, Gedeg District, Mojokerto Distric - Muchammad, Achmad; Hilmy Syahab; Afrida Sista Kurniasari; Alfi Lutfiah; Jayanti Devi Ikasari; Isna Qurrotul Aini (Khidmatuna (Jurnal Pengabdian Kepada Masyarakat), 2023)
This training aims to develop certain skills, knowledge and attitudes in the method used in the training, namely the ABCD (Asset Based Community Development) method, which is an approach to community development that has a big goal in trying to create a social life order in development efforts in community environment. The results obtained from this training are the effective implementation of training on making cellphone stands, so that POSPAUD mothers are able to acquire skills and expertise in making cellphone stands. The reason that community members, especially POSPAUD mothers in Beratwetan Village, are motivated to become entrepreneurs in the field of handicrafts is more due to the background of housewives who have a lot of free time. Besides that, it also has a selling price on the market. This motivates housewives to become handicraft entrepreneurs with the aim of improving the economy in the village. To measure the level of entrepreneurial motivation, you need a great sense of self-confidence to be able to set up a business after gaining skills, being able to be task and result oriented, having the courage to take risks, having a leadership spirit, being able to innovate, being creative and having an orientation towards the future. in the future. Therefore, this training activity is an effort that can be made to empower the community in Beratwetan Village so that it can increase community income.